Surface antigens of Toxoplasma gondii: variations on a theme. - Lekutis, C; Ferguson, D; Grigg, M; Camps, M; Boothroyd, J (2001)
Toxoplasma gondii is an obligate intracellular protozoan parasite with an exceptionally broad host range. Recently, it has become apparent that the number of surface antigens (SAGs) it expresses may rival the number of genera it can infect. Most of these antigens belong to the developmentally regulated and distantly related SAG1 or SAG2 families. The genes encoding the surface antigens are distributed throughout the T. gondii genome, with remarkably little polymorphism observed at each locus. Results from a number of studies have suggested that the surface antigens play an important role in the biology of the parasite. For example, SAG3 null mutants generated by targeted disruption provide convincing evidence that this surface antigen, at least, functions during parasite attachment. Analyses of a SAG1 knockout in rodents, however, indicate that this surface antigen may play a crucial role in immune modulation or virulence attenuation. The current understanding of the SAG1 and SAG2 families will be discussed here.